Purification of Olive Mill Wastewater Using Microfiltration Membrane Technology - Petrotos, Konstantinos B.; Lellis, Themistocles; Kokkora, Maria I.; Gkoutsidis, Paschalis E. (Journal of Membrane and Separation Technology, 2014)
Olive mill wastewater (OMWW), a by-product of the olive oil extraction process, is a severe polluting waste, but also a source of antioxidants; polyphenols, especially hydroxytyrosol. This study aimed at investigating the potential of microfiltration (MF) for separating the polyphenols from OMWW. OMWW treatment consisted of a preliminary centrifugation step, followed by MF for the separation of fats and polyphenols.Two types of ceramic MF membranes were used. MF flux ranged between 78 and 95 kg m-2 h-1, indicating the applicability of the described process on commercial scale. Better results were obtained with MF membrane of 50 nm pore size, due to its higher porosity compared to the membrane of 200 nm pore size. The optimum operative conditions were transmembrane pressure of 3.5 bar, flow rate of 10 m s-1, and temperature of approximately 55 °C. A 3-month storage of OMWW prior to treatment resulted in a 20% decrease in permeate flux, indicating that direct processing of the OMWW is necessary. Membrane pollution was not a problem for MF operation and did not affect membrane permeability significantly. Restoring the permeability of water to baseline levels after each use, confirmed the successful cleaning regime applied. The microfiltrate was an excellent antioxidant, which contained useful polyphenols, including hydroxytyrosol, tyrosol, p-coumaric acid, caffeic acid and catechin.